Analisis Aspek Teknis dan Teknologi dalam Studi Kelayakan Bisnis Restoran Dadar Beredar di Kawasan Jababeka - Kurniawan, Rachman Catur; Ramdhanni, Dhimas; Rohmah, Fitria Nur; Supriadi, Reza Aurora; Yuhafidin, Hafid; Setiawan, Muhammad Rizal; Tolib, Muhammad Abu; Herudin, Herudin; Setiawan, Indra (Proceeding Mercu Buana Conference on Industrial Engineering, 2025)
The fast food industry in Indonesia has experienced rapid growth in line with lifestyle changes that prioritize convenience. This study aims to evaluate the technical aspects of operational feasibility in the Dadar Beredar restaurant business, Jababeka branch, Cikarang. The research method used is a case study with a qualitative approach through field observations, interviews with management and staff, and customer surveys using the Customer Satisfaction Index (CSI) method. The results indicate that technical aspects such as strategic location selection, efficient kitchen layout, the use of QR code technology in ordering and transaction systems, as well as operational cleanliness and safety, have been optimally implemented. The CSI score of 77.59% reflects a customer satisfaction level categorized as satisfied, which also serves as an indicator that the business is technically feasible to operate and develop. This study recommends continuous improvements in service quality and periodic technical evaluations to strengthen Dadar Beredar's position in the fast food industry.